Estimativas de parâmetros genéticos, correlações e seleção de progênies segregantes de soja em diferentes épocas de semeadura. - Carvalho, Layara Santana de (2021)
Plant breeding programs aim to select genotypes with superior performance, with high productive potential, resistance to biotic and abiotic stresses. The productive potential of a progeny is influenced by the genetic constitution and its interaction with the environment, thus, it is important to obtain information about the behavior of this cultivar in different environments, such as location and sowing times. The present study aimed to estimate the genetic parameters and obtain phenotypic and genotypic correlations between soybean agronomic traits at different sowing dates for selection of segregating progenies from backcrosses The experiment was carried out in the field in the experimental area of the UFU Soybean Breeding Program, in the municipality of Uberlândia - MG, in the 2019/2020 season. One hundred and four RCF3 progenies from the Soybean Breeding Program - UFU were evaluated and the cultivars UFUS 6901, TMG 801 and BRSGO 7560 as controls. The design was a complete randomized block with three replications. The following agronomic characters were evaluated: number of days to flowering and to maturity, plant height at maturity, number of nodes on the main stem at maturity, number of productive nodes, number of pods per plant, grain production per plant, grain yield. The data were subjected to analysis of variance, means were grouped by the Scott-Knott test, phenotypic and genotypic correlations between traits were estimated and superior soybean progenies were selected. The existence of genetic variance at the level of 1% of probability was verified by the F test, for all the evaluated characters. The heritability parameters, the ratio between the genetic and environmental variation coefficients suggested favorable conditions for progeny selection for all characters in the different sowing times evaluated. Heritability was obtained between 39.08% PGP) and 92.76% (NDM) in November sowing, while in December sowing ranged from 55.83% (PROD) to 93.10% (NDM). The CVg/CVe ratio indicated favorable conditions for selection for NDF, NDM, APM, NNM and NN. It was verified the existence of correlations between the characters with a predominance of genetic causes, also suggesting the study of indirect selection in the evaluated progenies. In addition, a high magnitude negative relationship was observed between the traits directed to the cycle and productivity, indicating selection to reduce the number of days to flowering, days to maturity and greater grain yield. By the method of Mulamba and Mock (1978), it was verified smaller gain for the selection of progenies for reduction of the vegetative cycle and of complete development. However, using the genotype-ideotype distance index method, a greater balance was obtained for selection gain when considering all the agronomic characters studied, making it possible to select 25 superior progenies. To identify the superior progenies of soybean UFUS 3, UFUS 5, UFUS 19, UFUS 30, UFUS 45 and UFUS 97, which were selected as superior in relation to the others for the characters cycle reduction and grain yield.